2012
DOI: 10.1177/1557988311435835
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress Among Employed Fathers

Abstract: The aim of this study was to compare levels of psychological distress in employed single fathers relative to partnered fathers and to explore the role of psychosocial job quality, work-family conflict, and work-family facilitation as explanations for differences in distress. The data were collected from a cross-sectional telephone survey conducted in a Canadian city. Participants were 486 employed fathers with children living in the household. In addition to experiencing higher levels of psychological distress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…The caregiving stress process model (SPM), 12 , 13 multiple role strain/overload, 14 , 15 and time scarcity theories 16 posit mechanisms through which caregiving is thought to impact mental health. Additionally, caregiving being emotionally laden, is intrinsically interconnected to the relationship characteristics between the caregiver and care-recipient.…”
Section: Introductionmentioning
confidence: 99%
“…The caregiving stress process model (SPM), 12 , 13 multiple role strain/overload, 14 , 15 and time scarcity theories 16 posit mechanisms through which caregiving is thought to impact mental health. Additionally, caregiving being emotionally laden, is intrinsically interconnected to the relationship characteristics between the caregiver and care-recipient.…”
Section: Introductionmentioning
confidence: 99%
“…The group of parents of children under three is relatively small, and it therefore accounts for only a small share of the overall single parenthood employment gap; however, the use of long family leaves can have longer-term negative effects on employment and earnings (Thévenon & Solaz, 2013;Gangl & Ziefle, 2015), and there is evidence that long family leaves increase unemployment more strongly for single mothers than for partnered ones (Morosow & Jalovaara, 2019). Nevertheless, it is likely that the single parenthood employment gap reflects not just leave policies but a wider range of employment disincentives and work-life reconciliation challenges, which are relevant, especially in the lower educational groups (Janzen & Kelly, 2012;Kärkkäinen, 2011;Moilanen et al, 2019;Viitamäki, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Many working class employees cannot choose when to take breaks, have little control over their schedules, and cannot afford to take emergency paid leave (Williams & Boushey, 2010). Janzen and Kelly (2012) found that single fathers were more likely to be employed in low-wage occupations with less job security, autonomy, and reduced ability to access resources such as employer-provided, family-friendly benefits. The fathers in their study experienced greater work-family conflict than partnered fathers, which they suggested was due to the psychological strain of their work environments, where control over work was low, and the demands were high.…”
Section: Masculinity and Its Social Class Constructions: Work And Fam...mentioning
confidence: 99%